Pengaruh Penerapan Konsep Ecopreneurship Pada Mata Kuliah Kewirausahaan Terhadap Kemampuan Kolaborasi Mahasiswa Pendidikan IPA ULM - Yumna Iberahim (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
The purpose of this study was to determine the increase in students' collaboration skills through the application of the ecopreneurship concept in learning entrepreneurship courses for Science Education students at Lambung Mangkurat University (ULM). This study used a quantitative approach with a quasi-experimental method and applied a one group pre-test - post-test design, where ULM Science Education students were used as research subjects. Sample selection was carried out using a purposive sampling technique, while data collection was carried out through questionnaires. The data obtained were then analyzed using statistical methods, namely the N-Gain test, Paired Sample T-test, and correlation test to see the relationship between variables and evaluate the extent to which the application of the ecopreneurship concept influenced students' collaboration skills. The results of the analysis revealed that the application of the ecopreneurship concept had a significant impact on increasing students' collaboration skills, indicated by a significance value (2-tailed) of 0.000 which was below the threshold of 0.05. All indicators of collaboration skills, namely active contribution, work productivity, responsibility, flexibility and compromise, and mutual respect, experienced a significant increase after the application of the concept. These findings indicate that the integration of ecopreneurship in learning not only enriches students' learning process, but also prepares them to become responsible and sustainability-oriented entrepreneurs